Species Distribution Models as Tools for Community Empowerment and Informed Decision Making in Colombia’s Chocó Pacific Coast Fisheries - John Josephraj Selvaraj; Maria Alejandra Cifuentes-Ossa; Jeider Penna-Narvaez; Maira Alejandra Miranda-Parra; Fabio Andrés Herrera-Rozo (Fishes, 2023)
Changes in marine ecosystem dynamics have led to alterations in the availability of fish in established fishing grounds. Predictive models suggest their utility in understanding and predicting species distribution at varying depths and times of the year, significantly influencing regional fisheries management. Thus, access to information on oceanographic conditions, serving as a science-based decision-making support tool for artisanal fishers, has been identified as an adaptation strategy fostering social empowerment in the Colombian Pacific region. To address this need, an open-source WebGIS (geographic information system) was co-created to provide users with the results of species distribution models of marine fish species, aiming to expand knowledge of the ever-changing environment dynamics. The Chocó Artisanal Fishing Geovisor offers options for planning fishing operations and provides tools for understanding the results of species distribution models and resource management. By promoting informed decision making and community empowerment, it serves as a strategic response to marine environmental fluctuations, establishing itself as an essential tool for adapting to shifting marine conditions and ensuring food security.